The Effect of Self-Directed Video on Compression Quality Using the Sikomjaru Phantom - Kurnia Aji; M. Hanif Prasetya Adhi; Endiyono; Nurul Fatwati Fitriana (HealthCare Nursing Journal, 2025)
Cardiac arrest remains a major concern in healthcare due to its high mortality rate, with more than 100 deaths annually worldwide and 5% occurring in Indonesia. One recommended first aid method is Hands-Only CPR. This study aimed to evaluate the effect of Self-Directed Learning videos on Hands-Only CPR using SIKOMJARU on the compression quality of Hands-Only CPR performed by community health volunteers in Kalisaleh Village. The study employed a quasi-experimental design with a total sampling technique, involving 40 participants who received identical interventions. Compression quality was assessed using the Hands-Only CPR SOP from the American Heart Association (AHA), performed on the SIKOMJARU CPR education phantom. Data analysis was conducted using the Wilcoxon test, yielding significant results with a p-value of 0.000. The findings demonstrated that Self-Directed Learning videos on Hands-Only CPR using SIKOMJARU were effective in improving the compression quality of Hands-Only CPR. This method offered an efficient educational solution to enhance the capability of Kalisaleh Village health volunteers in managing out-of-hospital cardiac arrest cases.